The Methodology of Doppler-Derived Central Blood Flow Measurements in Newborn Infants - Koert A. de Waal (International Journal of Pediatrics)
Central blood flow (CBF) measurements are measurements in and around the heart. It incorporates cardiac output, but also measurements of cardiac input and assessment of intra- and extracardiac shunts. CBF can be measured in the central circulation as right or left ventricular output (RVO or LVO) and/or as cardiac input measured at the superior vena cava (SVC flow). Assessment of shunts incorporates evaluation of the ductus arteriosus and the foramen ovale. This paper describes the methodology of CBF measurements in newborn infants. It provides a brief overview of the evolution of Doppler ultrasound blood flow measurements, basic principles of Doppler ultrasound, and an overview of all used methodology in the literature. A general guide for interpretation and normal values with suggested cutoffs of CBFs are provided for clinical use.